PENGENALAN PEMASARAN DIGITAL DAN LAPORAN KEUANGAN BAGI PELAKU UMKM DI DESA RANCABUNGUR KABUPATEN BOGOR - Farradia, Yuary; Hadi, Delta; Prasetyo, Buntoro Heri; Supriyanto, Joko (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Managing business of Micro, Small, and Medium Enterprises (MSMEs) needs to balance between the marketing effort and financial management in term of financial  report  toward MSMEs sustainability. The MSMEs needs to up grade their marketing effort through implementing various digital marketing programs. On the other side, managing business also needs proper financial  report. MSMEs at Rancabungur Village, Bogor District still facing problem on  both marketing and financial report.  A community service was conducted to improve the skill of MSMEs through  introduction program of marketing digital and making a simple financial report.  About 20 MSMEs participants joined the workshop to understand the marketing digital and financial report at Rancabungur Village. Trough this workshop, participants were educated the best practice in utilizing various social media in digital marketing and also has introduction practice on creating the simple financial report of their particular business. Further workshop recommendation  about creating content on socia media  marketing as well as creating the profit and loss statement of the business are needed in future workshop series